Meet the Parents: A Parents’ Perspective on Product Placement in Children’s Films - Hudson, Simon (Journal of business ethics, 2008)
The ethics of advertising to children has been identified as one of the most important topics worthy of academic research in the marketing field. A fast growing advertising technique is product placement, and its use in children’s films is becoming more and more common. The limited evidence existing suggests that product placements are especially potent in their effects upon children. Yet regulations regarding placements targeted at children are virtually non-existent, with advertising guidelines suggesting that it remains the prime responsibility of the parents to provide guidance for children. This study measured the ethical evaluations of parents in the UK and Canada regarding product placements in children’s films. After exposing parents to a four-type typology of product placements, results show that explicit placements of ethically charged products were perceived as the most unethical type of placements. Parents in the UK were more sensitive to the use of the technique and there was a significant difference in relativism between the two groups. Both sets of respondents would like to see more regulation on the use of placements, especially placements of alcohol, tobacco and fast foods.